A Holistic Approach to Blood Glucose Management: Foot Exercise and Laughter Therapy in Older Adults with Type II Diabetes Mellitus - Pastari, Marta; Martini, Sri; Jamila, Jamila; Wibowo, Wahyu Dwi Ari; Meilina (International Journal Scientific and Professional, 2025)
This study compares the effectiveness of foot exercise and laughter therapy in reducing blood glucose levels in older adults with Type II Diabetes Mellitus. The objective is to determine which intervention has a greater impact on lowering blood glucose and promoting overall well-being. An independent samples t-test was conducted to compare the reduction in mean blood glucose levels between two intervention groups: foot exercise and laughter therapy. The assumption of equal variances was met based on the results of Levene’s test (p > 0.05). Both interventions resulted in significant reductions in blood glucose levels, but laughter therapy showed a slightly greater reduction. Foot exercise improved insulin sensitivity and glucose uptake, but may not be suitable for individuals with mobility issues. In contrast, laughter therapy not only reduced blood glucose levels but also promoted psychological benefits such as improved mood and reduced anxiety, which are crucial for diabetes management. The accessibility and lower physical demands of laughter therapy make it an attractive option for older adults, especially those with physical limitations. The findings suggest that laughter therapy offers a more holistic approach to diabetes management by addressing both physical and emotional well-being. This study highlights the potential of laughter therapy as a sustainable, low-impact intervention for improving health outcomes in older adults with Type II Diabetes Mellitus.